Modified melamine sponge capable of efficiently recovering high-viscosity oil and preparation method of modified melamine sponge
By combining the combination of graphite oil coke with polymailing siliconane and curing agent, the modified melamine sponge is prepared to solve the problem of high high viscosity oil recovery costs of sea crude oil leakage, and achieve high -efficiency and low -cost oil recovery. Promote the reuse of waste and the safety of the environment.
Patent Information
- Application Number
- CN202411359908.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-24
AI Technical Summary
The prior art is costly and difficult to effectively recover high viscosity oil when dealing with offshore crude oil leakage, which poses safety and environmental risks.
By combining petroleum -based graphite with polymailing siliconane and curing agent, modified melamine sponges are prepared, and high -efficiency recovery and high viscosity oil is used to use its good light thermal conversion capacity and hydrophobic oil absorption capacity.
The purpose of high -efficiency recycling high viscosity oil has been achieved, the cost is reduced, the safety and environmental problems brought by the leakage of maritime crude oil, and promoting the reuse of waste.
Smart Images

Figure CN119350707A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of melamine sponge modification, and in particular to a modified melamine sponge for efficiently recovering high-viscosity oil and a preparation method thereof. Background Art
[0002] Frequent oil spills at sea, the oily wastewater they produce, and the large-scale marine fires they cause have had a serious impact on human health and the ecological environment. Currently, superhydrophobic and oleophilic sponges modified with polyurethane (PU) sponges or melamine (MS) sponges are often used as oil-absorbing materials. These materials are characterized by high separation efficiency, good mechanical stability, low cost, and easy operation, and are therefore widely used.
[0003] For example, the patent with publication number CN111229168A discloses a method for recovering high-viscosity leaked crude oil using graphene-based materials, which uses melamine and graphene in combination to achieve rapid, sufficient and complete adsorption of crude oil. However, graphene is expensive, and in the face of frequent crude oil leaks, its cost is a huge challenge.
[0004] Therefore, there is still a need to explore low-cost but effective solutions or materials to deal with frequent crude oil spills. Summary of the invention
[0005] The present invention provides a modified melamine sponge for efficiently recovering high-viscosity oil and a preparation method thereof. The modified melamine sponge obtained by using waste petroleum coke has good photothermal conversion ability and good hydrophobic oil absorption ability, and can achieve the purpose of recycling oil by adsorption; at the same time, it turns waste into treasure, solves the safety environment and can also solve the problem of offshore crude oil leakage.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] The invention provides a preparation method of a modified melamine sponge for efficiently recovering high-viscosity oil, comprising: adding graphitized petroleum coke, polydimethylsiloxane and a curing agent to n-hexane in sequence under stirring at room temperature, immersing the mixture in melamine sponge after uniform mixing, and then drying and curing to obtain the modified melamine sponge.
[0008] Petroleum coke is a by-product obtained during the fluidized catalytic cracking of petroleum. It is an amorphous carbon or a highly aromatized high molecular carbide containing tiny graphite crystals in needle-like or granular structures. The applicant hopes to use waste petroleum coke to achieve efficient recovery of high-viscosity oil, but considering that petroleum coke itself is not a photothermal material, it is difficult to quickly reduce the viscosity of high-viscosity oil under light to achieve the purpose of adsorption and recovery of high-viscosity oil. However, considering that petroleum coke contains a small amount of graphite crystals, the applicant speculates that increasing the graphite crystal content in petroleum coke by graphitization may achieve the effect of graphene, a typical photothermal material.
[0009] Therefore, the petroleum coke is graphitized and the porous structure of the melamine sponge is utilized, and hydrophobic polydimethylsiloxane is added to obtain a modified melamine sponge. The graphitized petroleum coke is added first, and then the polydimethylsiloxane is added, so that the polydimethylsiloxane is evenly wrapped on the surface of the melamine skeleton and locks the free graphitized petroleum coke in the middle layer.
[0010] The modified melamine sponge obtained by the method provided in the present application has good photothermal conversion ability and good hydrophobic oil absorption ability, which can achieve the purpose of cyclic adsorption and recovery of oil, and is suitable for solving the problem of offshore crude oil leakage.
[0011] Preferably, the preparation method of the graphitized petroleum coke comprises: acid washing, drying and grinding the petroleum coke block into 200 mesh petroleum coke powder, and then keeping it at 2200-2500° C. for 12-16 hours under an inert atmosphere to obtain graphitized petroleum coke.
[0012] Preferably, the temperature is raised to 2200-2500° C. at a rate of 10° C. / min, maintained at that temperature for 12-16 hours, and then cooled to room temperature at a rate of 2° C. / min before being taken out.
[0013] Further preferably, the preparation method of the graphitized petroleum coke comprises: acid washing and drying the petroleum coke block and then grinding it into 200 mesh petroleum coke powder, then heating it to 2400°C at 10°C / min under an inert atmosphere and keeping it for 14 hours, then cooling it to room temperature at a cooling rate of 2°C / min and taking it out to obtain the graphitized petroleum coke.
[0014] Preferably, the inert atmosphere is nitrogen or argon, and the acid washing is carried out in 1M hydrochloric acid for 20 to 40 minutes.
[0015] Preferably, the grinding method is ball milling at 300-400 r / min for 8-10 hours.
[0016] Further preferably, the grinding method is ball milling at 350 r / min for 8 hours.
[0017] Preferably, the mass ratio of the graphitized petroleum coke, polydimethylsiloxane and curing agent is (0.01-0.07):10:1.
[0018] Further preferably, the mass ratio of the graphitized petroleum coke, polydimethylsiloxane and curing agent is (0.05-0.07):10:1.
[0019] Preferably, the drying and curing temperature is 110-130° C., and the drying and curing time is 2-3 hours.
[0020] More preferably, the drying and curing temperature is 120° C., and the drying and curing time is 2 hours.
[0021] Preferably, the curing agent is any one of methyltrichlorosilane, dibenzoyl peroxide, dicumyl peroxide, and titanate.
[0022] The invention also provides a modified melamine sponge prepared by the preparation method.
[0023] Preferably, the modified melamine sponge comprises an innermost melamine skeleton and an outermost polydimethylsiloxane membrane, and a large number of graphitized petroleum coke particles are disposed between the melamine skeleton and the polydimethylsiloxane membrane, wherein a portion of the graphitized petroleum coke particles are fused with the polydimethylsiloxane membrane.
[0024] In addition to some graphitized petroleum coke particles fused with polydimethylsiloxane and free graphitized petroleum coke particles located between the melamine skeleton and the polydimethylsiloxane membrane, there are also some graphitized petroleum coke particles attached to the outside of the polydimethylsiloxane membrane. This may be due to the inability of graphitized petroleum coke particles to maintain a high degree of dispersion in the mixed liquid.
[0025] Therefore, the present invention has the following beneficial effects:
[0026] (1) The preparation method provided by the present invention can successfully synthesize a modified melamine sponge with the advantage of efficiently recovering high-viscosity oil, providing a new idea for the adsorption and separation of high-viscosity oil leaked at sea.
[0027] (2) The present invention obtains graphitized petroleum coke by high-temperature calcination and reduced cooling rate, thereby increasing the graphite crystallinity of ordinary petroleum coke, improving the photothermal conversion capacity of petroleum coke, realizing the recycling of petroleum coke, and solving the problem of the accumulation of petroleum coke as a solid waste.
[0028] (3) The modified melamine sponge obtained by the present invention has good photothermal conversion ability and good hydrophobic oil absorption ability, which can achieve the purpose of cyclic adsorption and recovery of oil, and is suitable for solving the problem of offshore crude oil leakage. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 SEM images, where a is 0-PC@PDMS@MS, b is 10-PC@PDMS@MS, c is 30-PC@PDMS@MS, d is 50-PC@PDMS@MS, e is 70-PC@PDMS@MS, and f is the density distribution diagram of PC@PDMS@MS series modified melamine sponges;
[0030] Figure 2 The contact angle diagrams of modified melamine sponges at different PC loadings, from left to right: 0-PC@PDMS@MS, 10-PC@PDMS@MS, 30-PC@PDMS@MS, 50-PC@PDMS@MS, 70-PC@PDMS@MS;
[0031] Figure 3 The graph shows the adsorption capacity of modified melamine sponge to different oils (or organic solvents) at different PC loadings;
[0032] Figure 4 is the relationship between the adsorption capacity of 10-PC@PDMS@MS sponge and oil density;
[0033] Figure 5 This is a process diagram of carbon tetrachloride adsorption on 50-PC@PDMS@MS;
[0034] Figure 6 This is the process diagram of 50-PC@PDMS@MS adsorbing n-hexane;
[0035] Figure 7 Process diagram of gravity separation of a mixture of carbon tetrachloride and water by 50-PC@PDMS@MS;
[0036] Figure 8 The process diagram of 50-PC@PDMS@MS combined with a peristaltic pump to continuously separate a mixture of n-hexane and water;
[0037] Fig. 9 The wetting behavior of 50-PC@PDMS@CS in different liquids;
[0038] Fig.10 This is the wetting diagram of 50-PC@PDMS@CS in different pH solutions;
[0039] Fig.11 This is a process diagram of continuous extrusion of 50-PC@PDMS@CS under a gravity of 500g;
[0040] Fig.12 10 adsorption and extrusion cycle diagrams of 50-PC@PDMS@CS;
[0041] Fig.13 This is the efficiency diagram of 20 cycles of continuous gravity separation of 50-PC@PDMS@CS;
[0042] Fig.14 This is a diagram showing the process of MS absorbing butter at the bottom under light;
[0043] Fig.15 The process of 50-PC@PDMS@MS absorbing butter at the bottom under light;
[0044] Fig.16 The process and thermal imaging of MS sucking butter under light;
[0045] Fig.17 The process and thermal imaging of 50-PC@PDMS@CS absorbing butter under light;
[0046] Fig.18 Absorbance and solar spectra of MS, 0-PC@PDMS@CS, and 50-PC@PDMS@CS;
[0047] Fig.19 The temperature change process diagram of the heating and cooling of MS and 50-PC@PDMS@CS;
[0048] Fig. 20 Figure 2 is a diagram of the crude oil absorption process, where a is the process of 0-PC@PDMS@MS and 50-PC@PDMS@CS absorbing crude oil without light, b is the process of 0-PC@PDMS@MS and 50-PC@PDMS@CS absorbing crude oil under light, and c is the continuous process of 50-PC@PDMS@CS absorbing crude oil under light. DETAILED DESCRIPTION
[0049] The present invention is further described below in conjunction with specific embodiments. Those of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.
[0050] In this section, petroleum coke blocks were purchased from Hebei Yanxi Mineral Products Processing Plant. Sylgard-184 polydimethylsiloxane (PDMS) elastomer kit (including curing agent) was purchased from Dow Corning. Melamine sponge (MS) was purchased from Anyin Acoustic Materials Factory. Unless otherwise specified, other reagents were of analytical grade without further purification, and ultrapure water with a resistivity of 18 MΩ·cm was used in all experiments.
[0051] The soil for preparing the mud water came from the lawn soil of Hainan University; the crude oil came from Huizhou Petrochemical; the seawater came from Baishamen Beach in Haikou City; the butter came from Shenzhen Pinyuepin Food Co., Ltd.; n-hexane, dichloromethane, cyclohexane, carbon tetrachloride and methanol were purchased from Xilong Reagent; the peanut oil was Luhua peanut oil (5S physical pressing, first grade pressing).
[0052] [Example]
[0053] Example 1
[0054] S1. The petroleum coke block was washed with 1M hydrochloric acid for 30 minutes and then dried, then physically ground into powder, and then put into a planetary ball mill and set to 350r / min for 8 hours. After ball milling, it was taken out and passed through a 200-mesh sieve to obtain micro-nano-scale petroleum coke powder.
[0055] The petroleum coke powder obtained in S2 and S1 was heated to 2400°C at a rate of 10°C / min under a nitrogen atmosphere and kept at that temperature for 14 h, then cooled to room temperature at a rate of 2°C / min and taken out to obtain graphitized petroleum coke.
[0056] S3. Under stirring conditions at room temperature, 10 mg of graphitized petroleum coke obtained in S2, 10 g of polydimethylsiloxane, and 1 g of Dow Corning curing agent were added to 100 mL of n-hexane to obtain a mixed solution.
[0057] S4. Immerse a 2cm×2cm×3cm melamine sponge in the mixed solution in S3, stir for 20min, and then transfer to an oven for curing at 120°C for 2h to obtain a modified melamine sponge, which is recorded as 10-PC@PDMS@MS.
[0058] Example 2
[0059] This embodiment is basically the same as Embodiment 1, except that 30 mg of graphitized petroleum coke is used in S3, which is recorded as 30-PC@PDMS@MS.
[0060] Example 3
[0061] This embodiment is basically the same as Embodiment 1, except that 50 mg of graphitized petroleum coke is used in S3, which is recorded as 50-PC@PDMS@MS.
[0062] Example 4
[0063] This embodiment is basically the same as Embodiment 1, except that 70 mg of graphitized petroleum coke is used in S3, which is recorded as 70-PC@PDMS@MS.
[0064] Example 5
[0065] This embodiment is basically the same as embodiment 3, except that in S2: the temperature is raised to 2200°C at a rate of 10°C / min and kept at that temperature for 14h, then cooled to room temperature at a rate of 2°C / min and taken out to obtain graphitized petroleum coke.
[0066] Comparative Example 1
[0067] This comparative example is basically the same as Example 1, except that the addition of graphitized petroleum coke is eliminated, and is recorded as 0-PC@PDMS@MS.
[0068] Comparative Example 2
[0069] Untreated melamine sponge, denoted as MS.
[0070] Comparative Example 3
[0071] S1. The petroleum coke block was washed with 1M hydrochloric acid for 30 minutes and then dried, then physically ground into powder, and then put into a planetary ball mill and set to 350r / min for 8 hours. After ball milling, it was taken out and passed through a 200-mesh sieve to obtain micro-nano-scale petroleum coke powder.
[0072] S2. Under stirring conditions at room temperature, 50 mg of the petroleum coke powder obtained in S1, 10 g of polydimethylsiloxane, and 1 g of Dow Corning curing agent were added to 100 mL of n-hexane to obtain a mixed solution.
[0073] S2. Immerse a 2cm×2cm×3cm melamine sponge in the mixed solution in S2, stir for 20 minutes, and then transfer to an oven for curing at 120°C for 2 hours to obtain a modified melamine sponge.
[0074] Comparative Example 4
[0075] This comparative example is basically the same as Example 3, except that in S2: the temperature is raised to 2000°C at a rate of 10°C / min and kept at that temperature for 14h, then cooled to room temperature at a rate of 2°C / min and taken out to obtain graphitized petroleum coke.
[0076] Comparative Example 5
[0077] This comparative example is basically the same as Example 3, except that in S2: the temperature is raised to 2600°C at a rate of 10°C / min and kept at that temperature for 14h, then cooled to room temperature at a rate of 2°C / min and taken out to obtain graphitized petroleum coke.
[0078] Comparative Example 6
[0079] This comparative example is basically the same as Example 3, except that in S2: the temperature is raised to 2400°C at a rate of 10°C / min and kept at that temperature for 14h, then cooled to room temperature at a rate of 5°C / min and taken out to obtain graphitized petroleum coke.
[0080]
Performance test
[0081] 1. Morphology composition
[0082] The melamine sponges obtained in Examples 1 to 4 and Comparative Example 1 were subjected to SEM analysis, and the results are as follows: Figure 1 Observation Figure 1 a It can be seen that the surface of the 0-PC@PDMS@MS skeleton is smooth, and the surface of the MS skeleton is covered with a layer of PDMS, but the three-dimensional porous structure is still retained. Figure 1 b~e are modified melamine sponges with different PC loadings. With the increase of PC loading, the roughness of the skeleton of the modified melamine sponge increases, which is conducive to the formation of superhydrophobic structure.
[0083] Furthermore, in Figure 1 It can be found in Figure f that the density of the modified melamine sponge of the PC@PDMS@MS series increases with the increase of PC loading. When the density of the sponge decreases, its oil absorption capacity will decline, so a moderate PC loading can ensure better performance.
[0084] 2. Wettability
[0085] The wettability of modified melamine sponge is crucial to the oil-water separation performance. To this end, the contact angle test of the modified melamine sponge of PC@PDMS@MS series was carried out, and the results are shown in Figure 2 Observation Figure 2 It can be seen that with the increase of PC loading, the appearance color of the modified melamine sponge becomes darker. In addition, the contact angles of 0-PC@PDMS@MS, 10-PC@PDMS@MS, 30-PC@PDMS@MS, 50-PC@PDMS@MS, and 70-PC@PDMS@MS are 130.93°, 139.56°, 144.75°, 150.88°, and 151.36°, respectively. This result corresponds to the SEM results. With the increase of PC loading, the roughness of the skeleton of the modified melamine sponge increases, so that the contact angle becomes larger and the hydrophobicity is enhanced. When the PC loading reaches 50 mg, the corresponding 50-PC@PDMS@MS contact angle is greater than 150°, meeting the super-hydrophobic requirements; subsequently, the PC loading is increased, and the angle of the contact angle changes less. Therefore, when the PC loading is 50 mg, the corresponding 50-PC@PDMS@MS has the best hydrophobicity.
[0086] 3. Oil-water separation capability and stability
[0087] ① Determination of adsorption capacity: Weigh the PC@PDMS@MS series modified melamine sponge to obtain m0. Then, immerse the PC@PDMS@MS series modified melamine sponge in n-hexane / dichloromethane / cyclohexane / peanut oil / carbon tetrachloride / methanol, and take out and weigh the modified melamine sponge quickly after adsorption equilibrium is reached to obtain M0.
[0088] According to formula (1), the adsorption amount Q of PC@PDMS@MS series modified melamine sponge for different oils or organic solvents is calculated. m :
[0089]
[0090] Wherein, m0 represents the mass of PC@PDMS@MS series modified melamine sponge before adsorption equilibrium, g; M0 represents the mass of PC@PDMS@MS series modified melamine sponge after adsorption equilibrium, g; Q m It represents the adsorption capacity of PC@PDMS@MS series modified melamine sponge, g / g.
[0091] ② Determination method of recyclability and recycling performance:
[0092] The 50-PC@PDMS@MS sponge was weighed to obtain m0. Subsequently, the 50-PC@PDMS@MS sponge was completely immersed in the non-volatile peanut oil. After adsorption equilibrium, it was taken out and weighed to obtain M0; the adsorption amount Q was calculated according to formula (1): m .
[0093] The peanut oil adsorbed by the saturated 50-PC@PDMS@MS sponge in step 1) was squeezed out and weighed again to obtain m1; without drying, it was directly immersed in the peanut oil in step 1) again, and after reaching the second adsorption equilibrium, it was taken out and weighed to obtain M1; this process was recorded as the first extrusion-adsorption cycle.
[0094] Repeat step 2) ten times and calculate the adsorption amount Q of each cycle according to formula (2): an , calculate the residual oil amount Q after each cycle according to formula (3) b(n-1) , calculate the extrusion-adsorption cycle efficiency ε according to formula (4):
[0095]
[0096] Where n is the total number of extrusion-adsorption cycles; m n represents the mass of 50-PC@PDMS@MS sponge after extrusion at the nth extrusion-adsorption cycle, g; M n represents the mass of 50-PC@PDMS@MS sponge after adsorption equilibrium at the nth extrusion-adsorption cycle, g; Q anrepresents the adsorption amount of the nth extrusion-adsorption cycle, g / g; Q b(n-1) represents the residual oil content after the (n-1)th extrusion-adsorption cycle, g / g; Q m represents the adsorption capacity of 50-PC@PDMS@MS sponge, g / g; ε represents the extrusion-adsorption cycle efficiency of 50-PC@PDMS@MS sponge, %.
[0097] ③ Method for determining the separation efficiency of heavy oil: 20 mL of methylene blue dyed water (methylene blue 1 mg / L) and 10 mL of Sudan red dyed carbon tetrachloride (Sudan red 1 mg / L) were mixed to obtain an oil-water mixture, and the following separation experiment was performed. A 1 cm × 1 cm × 1 cm 50-PC@PDMS@MS sponge was placed in the neck of a long-necked funnel to form a gravity-driven one-way oil-water separation device (such as Figure 7 As shown). Pour the oil-water mixture into a long-necked funnel to collect the separated oil. Calculate the separation efficiency η according to formula (5):
[0098]
[0099] Wherein, C1 represents the weight of oil in the oil-water mixture before separation by 50-PC@PDMS@MS sponge, g; C0 represents the weight of oil in the oil-water mixture after separation by 50-PC@PDMS@MS sponge, g; η represents the separation efficiency of 50-PC@PDMS@MS sponge, %.
[0100] ④ Method for determining the ability of light oil to continuously separate oil and water: 20 mL of methylene blue-dyed water (methylene blue 1 mg / L) and 10 mL of Sudan red-dyed n-hexane (Sudan red 1 mg / L) were mixed to obtain an oil-water mixture; an intelligent suction system based on a peristaltic pump (such as Figure 8 Specifically, the rubber tube was combined with the 50-PC@PDMS@MS sponge and immersed in the prepared oil-water mixture, and a pressure difference was generated by suction with a peristaltic pump, so that the 50-PC@PDMS@MS sponge separated the oil from the oil-water mixture.
[0101] ⑤ Stability determination method in different media: 5 pieces of 1cm×1cm×1cm 50-PC@PDMS@MS sponges were placed on green tea, soy milk, coffee, sea water and muddy water, and photographed and recorded. After standing for 7 hours, photographed and recorded again.
[0102] ⑥ Corrosion resistance determination method: Place a 1cm×1cm×1cm 50-PC@PDMS@MS sponge into aqueous solutions with different pH values (pH=1, 3, 5, 7, 9, 11, 13) and take photos. After standing for 7 hours, take photos again. The solutions with different pH values are prepared by sodium hydroxide and hydrochloric acid to obtain the corresponding solutions with different pH values; and the different pH values are distinguished by dyeing with food-grade pigments (compound colorants: bright red, fruit green, sky blue and lemon yellow).
[0103] 3.1 Oil-water separation capability
[0104] The oil absorption capacity of modified melamine sponge is also crucial to the oil-water separation performance. The oil absorption capacity of modified melamine sponge was evaluated according to the measurement method shown in ① above, and the results are as follows:
[0105] Figure 3 The figure shows the adsorption capacity of modified melamine sponges for different oils (or organic solvents) at different PC loadings. It can be observed that as the PC loading increases, the oil absorption capacity of the modified melamine sponges in the PC@PDMS@MS series gradually decreases. Among them, the adsorption capacity of 0-PC@PDMS@MS for carbon tetrachloride can reach 29.82g / g, while the adsorption capacity of 70-PC@PDMS@MS is only 10.87g / g.
[0106] This result is consistent with the BET result. When the loading amount increases, the density of the sponge decreases and the oil absorption capacity decreases. Specifically, due to the PC loading, the MS pore size becomes smaller, and part of the position originally occupied by the oil is replaced by PC, which makes the PC@PDMS@MS absorb less oil. Therefore, the oil absorption capacity of the modified melamine sponge of the PC@PDMS@MS series will decrease with the increase of PC loading amount. In addition, combined with Figure 4 Taking the relationship between the adsorption capacity of 10-PC@PDMS@MS and oil density as an example, it can be seen that the oil absorption capacity of 10-PC@PDMS@MS is also related to the density of different oils; the greater the density of the oil, the stronger the oil absorption capacity of 10-PC@PDMS@MS.
[0107] Furthermore, the oil-water separation ability of 50-PC@PDMS@MS was tested according to the determination methods shown in ③ to ④ above, and the results are as follows:
[0108] observe Figure 5 and Figure 6It can be seen that 50-PDMS@PC@MS can quickly adsorb n-hexane in a mixture of n-hexane and water without absorbing water; similarly, 50-PDMS@PC@MS can also adsorb carbon tetrachloride in a mixture of carbon tetrachloride and water, and has an obvious silver mirror phenomenon in water. These phenomena indicate that the PDMS@PC@MS series of modified melamine sponges can achieve the ability to adsorb, separate and hydrophobic heavy oil or light oil-water mixtures. In order to better test the ability of 50-PDMS@PC@MS to separate heavy oil from oil-water mixtures, a mixture of carbon tetrachloride and water was subjected to gravity-driven separation, and the results are shown in the figure. Figure 7 As shown. As the oil-water mixture is poured in, carbon tetrachloride permeates downward through 50-PDMS@PC@MS and is separated, while water is trapped above 50-PDMS@PC@MS and does not permeate downward, and 10 mL of carbon tetrachloride is almost completely separated within 45 seconds. This phenomenon shows that 50-PDMS@PC@MS has good oil-water separation ability for heavy oil oil-water mixture. In addition, by combining 50-PDMS@PC@MS with a peristaltic pump into a continuous oil-water separation device, the light oil oil-water mixture is continuously separated. As shown Figure 8 As shown, within 21 seconds, the oil-water separation device quickly separated 10 mL of n-hexane from the oil-water mixture; this indicates that the oil-water separation device has a better separation effect on the oil-water mixture of light oil.
[0109] 3.2 Stability
[0110] In order to investigate the stability of 50-PC@PDMS@MS under different liquid environments, different acidity and alkalinity and external force extrusion, the tests were carried out according to the determination methods shown in ②, ③, ⑤ and ⑥ above.
[0111] Fig. 9 The wettability of 50-PC@PDMS@MS in different liquid environments was demonstrated. It was observed that 50-PC@PDMS@MS could continuously float on green tea, soy milk, coffee, sea water and muddy water and remain without penetrating into the liquid surface, indicating that 50-PC@PDMS@MS has good hydrophobic properties in different liquid environments.
[0112] Fig.10 The wettability of 50-PC@PDMS@MS in different pH environments was demonstrated. It was observed that 50-PC@PDMS@MS could continue to float stably on the surface in environments of pH = 1, 3, 5, 7, 9, 11, and 13, indicating that 50-PC@PDMS@MS has good acid and alkali resistance.
[0113] Furthermore, repeated extrusion tests were performed on 50-PC@PDMS@MS to determine its extrusion resistance. Fig.11As shown in the figure: under the continuous external force, the 50-PC@PDMS@MS sponge can quickly return to its original shape. This result is conducive to the extrusion adsorption cycle treatment of leaked oil. Therefore, the applicant also tested the adsorption extrusion cycle performance of 50-PC@PDMS@MS on peanut oil, and the results are shown in the figure. Fig.12 It can be observed that the adsorption cycle capacity of 50-PC@PDMS@MS for peanut oil can reach more than 7.97g / g, and the desorption cycle capacity is less than 1.5g / g; this shows that 50-PC@PDMS@MS has good adsorption and extrusion performance and can be used for multiple adsorption and extrusion separation of oil products.
[0114] In addition, the continuous separation capability of 50-PC@PDMS@MS for gravity separation of a mixture of carbon tetrachloride and water was tested. Fig.13 It shows that 50-PC@PDMS@MS can continuously separate oil-water mixtures and has good continuous oil-water separation performance.
[0115] 4. Photothermal assisted adsorption and separation of high viscosity oil
[0116] ① High viscosity oil adsorption test method: Use a xenon lamp light source (CEL-HXF300-T3, China; 300-1100nm, 500w, 15A) to simulate a sun (1kW / m 2 ) to study the adsorption capacity of 50-PC@PDMS@MS sponge and MS sponge. Equal amounts of butter were placed on a 1cm thick 50-PC@PDMS@MS sponge and a 1cm thick MS sponge, and the xenon light source was turned on for 13 minutes to observe the adsorption of the two.
[0117] ② Determination of photothermal conversion capacity: A xenon lamp light source (CEL-HXF300-T3, China; 300-1100nm, 500w, 15A) was used to simulate a sun (1kW / m 2 ) to study the photothermal conversion ability of FPMA-PU sponge. To ensure the accuracy of the light intensity, an optical power meter (CEL-FZ-A, CEC Jin Yuan, China) was used for calibration. An infrared thermal imager was used to measure the temperature change of the material over time and record the cooling rate of the sample.
[0118] 1 mL of crude oil was dropped into 30 mL of water and then placed on the 0-PC@PDMS@MS sponge for adsorption with the light on and the light off.
[0119] 1 mL of crude oil was dropped into 30 mL of water and then placed on a 50-PC@PDMS@MS sponge for adsorption with the light on and the light off.
[0120] ③ Determination method of recycling capacity: Use a xenon lamp light source (CEL-HXF300-T3, China; 300-1100nm, 500w, 15A) to simulate a sun (1kW / m 2 ) to study the recovery capacity of 50-PC@PDMS@MS sponge. 15g crude oil and 30mL water were mixed as a crude oil spill simulant, and the 50-PC@PDMS@MS sponge and pump were assembled into a continuous oil-water separation device (such as Fig. 20 c), and conduct the following experiment. Turn on the xenon light source, add 50-PC@PDMS@MS sponge into the prepared simulant and start continuous recovery of crude oil. The mass of crude oil before separation is weighed as m a , weigh the mass of the separated crude oil as m b The recovery rate ε is calculated according to formula (6):
[0121]
[0122] Among them, m a is the mass of crude oil before separation, g; m b is the mass of crude oil after separation, g.
[0123] 4.1 High viscosity oil adsorption
[0124] The thermal conductivity of MS and 50-PC@PDMS@MS was tested. Fig.14 and Fig.15 As shown: After 13 minutes of illumination, MS cannot melt the butter, while 50-PC@PDMS@MS can melt a large part of the butter. Specifically, MS has weak photothermal conversion absorption capacity. Under illumination, the surface temperature of MS rises slowly and cannot rise too high, resulting in MS being unable to transfer more heat to the bottom. Therefore, the temperature at the bottom of MS cannot melt the butter. 50-PC@PDMS@MS has good photothermal conversion performance. Under illumination, the surface temperature of 50-PC@PDMS@MS rises rapidly, and it can quickly conduct heat downward, causing the temperature at its bottom to rise and reach a temperature that can melt the butter. The above results show that 50-PC@PDMS@MS has good thermal conductivity, can reduce the viscosity of the bottom oil and absorb oil.
[0125] The key reason why 50-PC@PDMS@MS has good thermal conductivity can be found in Table 1. It can be seen from Table 1 that Example 3 shows faster and larger butter absorption than Comparative Example 3, which proves that graphitization is the key to improving the photothermal performance of petroleum coke. As a result, 50-PC@PDMS@MS loaded with graphitized petroleum coke has better thermal conductivity, enabling it to quickly absorb high-viscosity oil.
[0126] The above results show that there is an important relationship between thermal conductivity and rapid adsorption of high-viscosity oil: the stronger the thermal conductivity, the shorter the time it takes to adsorb high-viscosity oil and the greater the amount of oil adsorbed.
[0127] Table 1 The process of sponge bottom absorbing butter under light
[0128]
[0129] The evaluation criteria in Table 1 are as follows:
[0130] No absorption at all: 0%;
[0131] Micro-absorption: 0-10%;
[0132] Small amount of absorption: 10-30%;
[0133] Larger absorption: 30-50%;
[0134] Absorption in large quantities: 50-80%;
[0135] Basic absorption: 80-90%;
[0136] Nearly complete absorption: more than 90%.
[0137] Furthermore, the high-viscosity oil absorption capacity of MS and 50-PC@PDMS@MS was tested to verify the above speculation on the correlation between thermal conductivity and rapid adsorption of high-viscosity oil.
[0138] like Fig.16 As shown in the figure, under the sunlight irradiation for 13 minutes, the butter on the MS surface hardly melted, and the temperature of the MS surface only reached 40℃ at most, which was unable to melt and adsorb the butter. Fig.17 As shown, after 2 minutes, the temperature of the 50-PC@PDMS@MS surface reached 60.3°C, and it can be seen that the butter in contact with the 50-PC@PDMS@MS surface began to melt. After 5 minutes, the surface temperature of 50-PC@PDMS@MS reached 67.7°C, and more than half of the butter was melted. After 7 minutes, the butter on the surface of 50-PC@PDMS@MS was almost melted and absorbed, and its surface temperature reached 74.9°C. The above results show that 50-PC@PDMS@MS can quickly adsorb high-viscosity oil in a short time and has a good ability to photothermally adsorb high-viscosity oil. At the same time, it is proved that the stronger the thermal conductivity, the stronger the photothermal conversion ability of the modified melamine sponge, and the corresponding time for adsorbing high-viscosity oil is shorter.
[0139] In addition, analysis of Table 2 also shows that graphitization is the key to improving the photothermal performance of petroleum coke.
[0140] Table 2 The process of sponge absorbing butter under light
[0141] sample Microabsorption time Small amount of absorption time Lots of absorption time Basic absorption time Example 3 1min 3min 5min 7min Example 5 1min 3min 5min 7min Comparative Example 2 No absorption at all No absorption at all No absorption at all No absorption at all Comparative Example 3 2min 4min 7min 10min Comparative Example 4 1min 3min 6min 8min Comparative Example 5 1min 3min 6min 8min Comparative Example 6 2min 4min 7min 9min
[0142] The evaluation criteria in Table 2 are as follows:
[0143] No absorption at all: 0%;
[0144] Micro-absorption: 0-30%;
[0145] Small amount of absorption: 30-50%;
[0146] Absorption in large quantities: 50-80%;
[0147] Basic absorption: 80~100%.
[0148] 4.2 Photothermal performance
[0149] The photothermal conversion ability of 50-PC@PDMS@MS is crucial for the adsorption of high-viscosity oil. In order to examine the photothermal performance of MS loaded with petroleum coke powder, the absorption properties of MS, 0-PC@PDMS@MS and 50-PC@PDMS@MS were tested. Fig.18 As shown in the figure, the light absorption capacity of MS and 0-PC@PDMS@MS is not much different; in the ultraviolet visible light range, the light absorption capacity of 0-PC@PDMS@MS is even lower than that of MS. However, the light absorption capacity of 50-PC@PDMS@MS can reach more than 85%. The results show that loading PDMS on MS almost does not change the light absorption capacity of the original MS; while loading PC can enhance the light absorption capacity of MS.
[0150] Furthermore, the thermal conversion capabilities of MS and PC@PDMS@MS were tested under one sun. Fig.19 As shown in the figure, within 180s under illumination, the temperature of the MS surface increased from 25.4℃ to 29℃, an increase of only 3.6℃. The temperature of the 50-PC@PDMS@MS surface increased from 26.7℃ to 82.9℃, an increase of 56.2℃. Within 60s after turning off the light, the temperature of the MS surface decreased from 29℃ to 25.5℃, a decrease of only 3.5℃. The temperature of the 50-PC@PDMS@MS surface decreased from 82.9℃ to 32.2℃, a decrease of 50.7℃. The results show that the thermal conversion capacity of MS is low; while 50-PC@PDMS@MS can not only heat up quickly under illumination, but also cool down quickly after turning off the light, and has strong thermal conversion capacity. The above results show that 50-PC@PDMS@MS has good photothermal performance and can be used for photothermal-assisted adsorption of high-viscosity oil tests.
[0151] 4.3 Simulated crude oil spill
[0152] Crude oil itself has a certain degree of blackness and can melt under light, but its melting speed is slow. Therefore, the applicant used 50-PC@PDMS@MS to quickly heat up under light to accelerate the melting and absorption of crude oil, and conducted adsorption tests on crude oil by MS without light and 50-PC@PDMS@MS under light.
[0153] like Fig. 20 As shown in a, in the absence of light, after 7 min, both 0-PC@PDMS@MS and 50-PC@PDMS@MS could not melt the crude oil on the water. Fig. 20 As shown in b, under 1 sun, after 7 minutes, 0-PC@PDMS@MS also cannot melt the crude oil on the water; while 50-PC@PDMS@MS can transfer heat to the bottom through heat transfer, melt the crude oil and absorb part of it. The results show that 50-PC@PDMS@MS has better melting and adsorption properties for crude oil under light.
[0154] 50-PC@PDMS@MS and a peristaltic pump were assembled into an oil-water separation device, and crude oil leakage was simulated to perform continuous adsorption and separation of crude oil. Fig. 20 As shown in Figure c, it can be seen that 50-PC@PDMS@MS can melt and absorb the crude oil in the contact part at 6 minutes. With the continuous suction under the action of the pump, after 9 minutes, the crude oil has been separated in the beaker; after 15 minutes, the weight of the separated crude oil increases, and the separated crude oil is about 6.7g. The above results show that 50-PC@PDMS@MS can continuously adsorb and separate crude oil, and has good performance in continuously separating high-viscosity oil.
Claims
1. A method for preparing a modified melamine sponge for efficiently recovering high-viscosity oil, characterized in that: include: Under stirring conditions at room temperature, graphitized petroleum coke, polydimethylsiloxane and a curing agent are sequentially added into n-hexane, mixed evenly and then immersed into a melamine sponge, which is then dried and cured to obtain a modified melamine sponge.
2. The preparation method according to claim 1, characterized in that The preparation method of graphitized petroleum coke comprises: acid-washing and drying the petroleum coke block and then grinding it into 200-mesh petroleum coke powder, and then keeping it at 2200-2500° C. for 12-16 hours under an inert atmosphere to obtain graphitized petroleum coke.
3. The preparation method according to claim 2, characterized in that: Raise the temperature to 2200-2500°C at 10°C / min, keep it at that temperature for 12-16h, then cool it down to room temperature at a cooling rate of 2°C / min and take it out.
4. The preparation method according to claim 2, characterized in that: The inert atmosphere is nitrogen or argon, and the acid washing is washing in 1M hydrochloric acid for 20 to 40 minutes.
5. The preparation method according to claim 2, characterized in that: The grinding method is ball milling at 300-400 r / min for 8-10 hours.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The mass ratio of the graphitized petroleum coke, polydimethylsiloxane and curing agent is (0.01-0.07):10:
1.
7. The preparation method according to any one of claims 1 to 5, characterized in that: The mass ratio of the graphitized petroleum coke, polydimethylsiloxane and curing agent is (0.05-0.07):10:
1.
8. The preparation method according to claim 1, characterized in that: The drying and curing temperature is 110-130° C., and the drying and curing time is 2-3 hours.
9. The modified melamine sponge obtained by the preparation method according to any one of claims 1 to 8.
10. The modified melamine sponge according to claim 9, characterized in that: The modified melamine sponge comprises an innermost melamine skeleton and an outermost polydimethylsiloxane film, a large number of graphitized petroleum coke particles are arranged between the melamine skeleton and the polydimethylsiloxane film, and a part of the graphitized petroleum coke particles are fused with the polydimethylsiloxane film.
Citation Information
Patent Citations
Method for recovering high-viscosity leaked crude oil by using graphene-based material
CN111229168A